Acute exacerbations of idiopathic pulmonary fibrosis and the role of corticosteroids - Brereton, Christopher J. (Breathe (Sheff), 2020)
An acute exacerbation of idiopathic pulmonary fibrosis (AEIPF) is a potentially fatal complication of an already debilitating disease. Management is currently centred on delivering excellent supportive care and identifying reversible triggers. Despite growing international awareness and collaboration, no effective therapies have been identified. Corticosteroids are often the mainstay of treatment; however, the evidence base for their use is poor. Here, we review our current understanding of the disease process and how to manage it, with a focus on the role of corticosteroid therapy.